PENGARUH LEVERAGE, CAPITAL INTENSITY, SALES GROWTH DAN FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - Sagala, Hilary Mika; Akhadi, Iman (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this study is to examine the effect of leverage, capital intensity, sales growth, profitability, institutional ownership, managerial ownership, executive characteristics, and company size on tax avoidance. The population of this study was all manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2023. The sample of this study was obtained using a purposive sampling method, where only 48 manufacturing companies listed on the Indonesia Stock Exchange that met all criteria, resulting in 144 data items used as the research sample. The data source in this study was obtained from the Indonesia Stock Exchange website. This study used a Weighted Least Squares (WLS) regression model to examine the effect of each variable on tax avoidance. Empirical evidence shows that the variables leverage (DAR), capital intensity (CIR), sales growth (SAG), profitability (ROA2), institutional ownership (IOW), managerial ownership (MOW), and company size (SZC) have an influence on tax avoidance as indicated by the significance value of the t-test results below 0.05. Meanwhile, the executive character variable (EXC) has no influence on tax avoidance efforts.